Boron nitride interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material and preparation method thereof
By introducing foam metal frames into the polytetrafluoroethylene composite material and assembling and modifying the interface of boron nitride, the problem of lubrication failure in the friction process of traditional polytetrafluoroethylene composite materials is solved, and high thermal conductivity, high wear resistance and high The interpenetrating lubricating material carried.
Patent Information
- Application Number
- CN202411586595.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Traditional PTFE composite materials fail lubrication during friction due to thermal deformation, pressure deformation and wear, and the thermal conductivity, mechanical strength and lubricating properties are limited by the PTFE continuous phase matrix.
By introducing a three-dimensional continuous foam metal skeleton and assembling and building boron nitride at the metal skeleton/PTFE interface to enhance interface bonding; at the same time, using boron nitride as a reinforcement filler to composite the polytetrafluorovinyl matrix, Improve its load-bearing capacity, wear resistance and thermal conductivity.
The prepared boron nitride interface assembly and decoration foam metal-polytetrafluoroethylene interpenetrating phase lubricating material has the characteristics of high thermal conductivity, high wear resistance and high load bearing. It is suitable for high-temperature lubricating materials in oil-free lubricating states and can be used to manufacture various Moving parts such as bearings, seals and other moving parts in corrosive media environments.
Smart Images

Figure CN119431978A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lubricating materials, and relates to a method for preparing an interpenetrating phase lubricating material, in particular to a method for preparing an interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material. Background Art
[0002] Polymer materials are used as solid lubricants due to their advantages such as low density, high specific strength, fatigue resistance, good self-lubrication and compatibility with foreign matter. Among them, polytetrafluoroethylene is widely used in friction parts such as mechanical seals, bearings, and gaskets due to its low friction, corrosion resistance, excellent chemical stability and high thermal stability. Due to the low thermal conductivity, poor wear resistance and creep of polytetrafluoroethylene, lubrication failure often occurs during the friction process due to thermal deformation, pressure deformation and wear. A common method for this is to use zero-dimensional, one-dimensional or two-dimensional functional fillers for composite modification to improve the wear resistance, thermal conductivity, mechanical strength and creep resistance of polytetrafluoroethylene resin. However, in traditional polytetrafluoroethylene composites, the low content of functional fillers is often insufficient to form a continuous phase, and the reinforcement effect on polytetrafluoroethylene is limited by the scale of the interface. In other words, polytetrafluoroethylene is still the only continuous phase in the composite material, resulting in its thermal conductivity, mechanical strength and lubrication properties being largely restricted by the polytetrafluoroethylene continuous phase matrix.
[0003] Interpenetrating phase composite materials are new materials in which two or more constituent phases are interconnected in a three-dimensional topological manner in a microstructure. In recent years, interpenetrating metal-polymer composite materials have begun to be designed and applied in the field of friction and wear because they can combine the dual-phase advantages of foam metal and polymer. Among them, the three-dimensionally connected foam metal is compounded with polytetrafluoroethylene to construct an interpenetrating phase composite material, which can break through the bottleneck problem that the reinforcement effect of traditional fillers is limited by the scale of the interface, and comprehensively improve the comprehensive performance of the composite material. CN101906549A discloses an embedded solid self-lubricating material based on porous foam metal, in which a solid lubricant is filled into the skeleton of the foam metal with an organic suspension, and then air-dried and cold-pressed and sintered to prepare the molding. The prepared composite material has the characteristics of light weight and high thermal conductivity of foam metal, and has the excellent lubrication performance and foreign body compatibility of the polymer base. However, due to the poor dispersibility of the organic suspension, it is inevitable that there are more incompletely filled pores in the dual-continuous phase composite material, which has a higher water absorption rate in the water environment, resulting in poor friction and wear performance; at the same time, the strength of the metal skeleton is easily damaged in the process of pressing the molten resin, resulting in insufficient mechanical strength.
[0004] For interpenetrating composite materials based on polytetrafluoroethylene, the main weakness is that the temperature required for polytetrafluoroethylene to sinter and melt to form a continuous phase is relatively high, usually above 330°C. Since the linear expansion coefficient of metal materials such as copper, aluminum, nickel, and iron is much smaller than that of polytetrafluoroethylene, there is often a large interface gap between the two during melting and cooling. Therefore, in the absence of interface protection, the transfer of stress and heat between the metal skeleton and polytetrafluoroethylene is limited, making it difficult to fully improve its load-bearing capacity, wear resistance, and thermal conductivity.
[0005] Based on this, the present invention provides an interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material and a preparation method thereof. On the basis of the metal skeleton / polytetrafluoroethylene interpenetrating phase composite system, boron nitride is used to assemble and construct the metal skeleton / polytetrafluoroethylene three-dimensional continuous interface to enhance the interface bonding between the two; on this basis, boron nitride is used as an added reinforcing filler to perform composite modification on the polytetrafluoroethylene matrix to further enhance its load-bearing capacity, wear resistance and thermal conductivity. The prepared foam metal-polytetrafluoroethylene dual continuous phase material modified by the interface assembly of boron nitride has the characteristics of high thermal conductivity, high wear resistance and high load-bearing capacity, and can be used for high-temperature lubricating materials under oil-free lubrication conditions, and can also be promoted and applied to the manufacture of moving parts such as bearings, seals, thrust washers, etc. serving in various corrosive media environments. Summary of the invention
[0006] The purpose of the present invention is to provide an interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material and a preparation method thereof in view of the problem that the commonly used composite modified polytetrafluoroethylene lubricating materials have poor comprehensive performance. By introducing a three-dimensional continuous foam metal skeleton, the thermal conductivity and load-bearing capacity of the polytetrafluoroethylene composite material are greatly improved; then the interface bonding is improved by the boron nitride interface assembly construction, and the transmission and dissipation of stress and friction heat during friction and wear are promoted; and on this basis, the composite modification of the polytetrafluoroethylene matrix by boron nitride is further performed to comprehensively improve the thermal conductivity and friction and wear performance of the composite material, and an interpenetrating phase lubricating material with a unique three-dimensional continuous metal skeleton-boron nitride-polytetrafluoroethylene interface structure and the advantages of high thermal conductivity, high wear resistance and high load-bearing comprehensive performance is obtained.
[0007] 1. Preparation of interpenetrating phase lubricating materials 1) Interface assembly: Add boron nitride to polytetrafluoroethylene emulsion and disperse it evenly to prepare assembly solution; immerse the foam metal in the assembly solution for 5-20 minutes under vacuum, then take it out and dry it in an environment of 70-110℃ for 5-20 minutes to remove the solvent; repeat the immersion-drying steps several times; 2) Matrix impregnation: Boron nitride is added to deionized water and dispersed evenly to obtain a boron nitride dispersion; the boron nitride dispersion is then added to a polytetrafluoroethylene emulsion and dispersed evenly to prepare a matrix liquid; the metal foam after interface assembly is immersed in the matrix liquid under vacuum for 10 to 60 minutes, then taken out and placed in an environment of 80 to 120°C for drying for 30 to 120 minutes to remove the solvent; the immersion-drying steps are repeated several times; 3) placing the composite material obtained in step 2) in a sintering furnace, heating it to 330-390° C., sintering it for 60-390 min, cooling it in the furnace, and then taking it out to obtain a boron nitride interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material.
[0008] In the above steps 1) to 3), the particle size of the boron nitride is 2-15 μm, and the thermal conductivity is 150-800 W / (m·K); the mass concentration of the polytetrafluoroethylene emulsion is 35%-65%, and the particle size of the polytetrafluoroethylene in the emulsion is 60-500 nm; the foam metal is one or more of nickel, copper, iron or iron-nickel alloy, the porosity is 90-99%, and the number of pores per inch (PPI) is 10-110.
[0009] The solid-liquid mass ratio of boron nitride to polytetrafluoroethylene emulsion in the assembly liquid is 5:1~2:1.
[0010] The mass ratio of boron nitride to polytetrafluoroethylene in the base liquid is 1% to 10%, and the concentration of the boron nitride dispersion is 0.5 to 5%.
[0011] 2. Structural Characterization of Interpenetrating Phase Lubricating Materials The surface structure, interface structure and wear morphology of the interpenetrating composite material were observed by optical fiber microscope, scanning electron microscope and X-ray spectrometer. Figure 1-3 shown.
[0012] Figure 1 The surface morphology of the interpenetrating metal-polytetrafluoroethylene lubricating material modified by the interface assembly of boron nitride in the present invention is shown in the figure. As can be seen from the figure, the metal skeleton in the interpenetrating composite material is tightly embedded by polytetrafluoroethylene, and the surface is smooth and dense, without obvious pores or cracks.
[0013] Figure 2 The interface structure of the interfacial assembly-modified metal foam-polytetrafluoroethylene interpenetrating lubricating material of the present invention is shown in the figure. As can be seen from the figure, lamellar boron nitride can be assembled and constructed on the surface of the metal skeleton after being dispersed in the polytetrafluoroethylene emulsion. The fluorine element on the surface of the metal skeleton that partially belongs to polytetrafluoroethylene is replaced by nitrogen and boron elements, proving the existence of boron nitride.
[0014] Figure 3This is the wear morphology of the interpenetrating phase composite material of metal foam-polytetrafluoroethylene modified by the interface assembly of boron nitride. In the figure, only the friction furrows along the horizontal sliding direction can be seen, and the interface between the metal skeleton and the polytetrafluoroethylene is still tightly bonded.
[0015] 3. Performance evaluation of interpenetrating phase lubricating materials 1. Thermal conductivity test The samples prepared in Examples 1 to 3 were machined into discs of φ12.7 mm×2 mm and tested on a thermal conductivity tester according to GJB / T1201.1-91. The data are listed in Table 1.
[0016] 2. Friction and wear performance The samples prepared in Examples 1 to 3 were machined into rectangular sheets of different thicknesses with a length of 30 mm and a width of 15 mm. The friction and wear properties were tested using a UMT friction and wear tester at an ambient temperature of 23±5°C. The upper specimen was a 316 stainless steel flat pin with a hardness of HRC56 and a diameter of 4.8 mm. It was reciprocated under a load of 100 N and a frequency of 8 Hz, with a single stroke of 5 mm and a total stroke of 300 m. The data are listed in Table 1.
[0017] Table 1 Properties of interpenetrating phase lubricating materials prepared in Examples 1-3 As shown in Table 1, the thermal conductivity of the interpenetrating phase lubricating material of metal foam-polytetrafluoroethylene modified by the boron nitride interface assembly prepared by the present invention is 0.72-2.60 W / (m·K), the friction coefficient is 0.09-0.15, and the wear rate is (1.0-4.3)×10 - 5 mm 3 / Nm. It can be seen that the metal foam-polytetrafluoroethylene interpenetrating phase lubricating material modified by boron nitride interface assembly has better thermal conductivity and friction and wear properties than the polytetrafluoroethylene / metal foam composite material without interface assembly, especially the thermal conductivity is far higher, and it also has excellent lubrication and wear resistance. In comparison, the lowest wear rate obtained in CN101906549A is 2.05×10 -5 mm / N·m, according to the present invention, the contact area is converted into a volume wear rate of 37 × 10 -5 mm 3 N·m, which is one order of magnitude higher than the wear rate of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The invention discloses a surface morphology of a boron nitride interface-assembled modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material.
[0019] Figure 2The invention discloses an interface structure of a boron nitride interface-assembled modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material.
[0020] Figure 3 The invention discloses the wear morphology of the interpenetrating lubricating material of metal foam and polytetrafluoroethylene modified by the interface assembly of boron nitride. DETAILED DESCRIPTION
[0021] Example 1 Take 55 g of boron nitride (size 5 μm, thermal conductivity 400 W / (m·K)), 60 g of nickel foam (porosity 96%, number of openings per inch 60) and 500 g of excess polytetrafluoroethylene emulsion (polytetrafluoroethylene particle size 50 nm, mass percentage 50%).
[0022] 1) Interface assembly Add 50g of boron nitride to 20g of polytetrafluoroethylene emulsion, stir magnetically for 2h at 50 rpm until fully dispersed, and prepare an assembly solution with a ratio of boron nitride to polytetrafluoroethylene of 5:1. Under a vacuum degree of -0.10MPa, immerse the metal skeleton in the assembly solution for 5min, then take it out and put it in an oven to dry at 80℃ for 5min to remove the solvent. Repeat the above immersion-drying steps twice.
[0023] 2) Matrix impregnation Add 5g of boron nitride to 95g of deionized water and disperse evenly. Then add 100g of boron nitride aqueous dispersion to 200g of polytetrafluoroethylene emulsion (the ratio of boron nitride to polytetrafluoroethylene is 5%), stir magnetically at 150 rpm for 5h until fully dispersed, and prepare the matrix liquid. Under a vacuum degree of -0.12MPa, immerse the interface-assembled foam metal skeleton in the matrix liquid for 10min, take it out, put it in an oven and dry it at 100℃ for 15min to remove the solvent. Repeat the above immersion-drying steps 3 times.
[0024] 3) Sintering The composite material was placed in a high-temperature sintering furnace dedicated to polytetrafluoroethylene and sintered at 375°C for 100 min. After cooling, a boron nitride interface assembled modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material was obtained. The properties are shown in Table 1 and the structural characterization is shown in Table 1. Figure 1-3 .
[0025] Example 2 Take 36 g of boron nitride (size 10 μm, thermal conductivity 600 W / (m·K)), 25 g of nickel foam (porosity 88%, number of pores per inch 100) and 400 g of excess polytetrafluoroethylene emulsion (polytetrafluoroethylene particle size 80 nm, mass percentage 40%).
[0026] 1) Interface assembly Add 30g of boron nitride to 7.5g of polytetrafluoroethylene emulsion, stir magnetically for 1h at 100 rpm until fully dispersed, and prepare an assembly solution with a ratio of boron nitride to polytetrafluoroethylene of 10:1. Under a vacuum degree of -0.04MPa, immerse the metal skeleton in the assembly solution for 8min, then take it out and put it in an oven at 75℃ for 15min to remove the solvent. Repeat the above immersion-drying steps once.
[0027] 2) Matrix impregnation 6g of boron nitride was added to 194g of deionized water and uniformly dispersed. Then, 200g of the aqueous dispersion of boron nitride was added to 300g of polytetrafluoroethylene emulsion (the ratio of boron nitride to polytetrafluoroethylene was 5%), and the mixture was stirred magnetically at 150 rpm for 5h until fully dispersed to prepare a matrix liquid. Under a vacuum degree of -0.05MPa, the foam metal skeleton after interface assembly was immersed in the matrix liquid for 60min, then taken out and placed in an oven for drying at 120°C for 120min to remove the solvent. The above immersion-drying steps were repeated 4 times.
[0028] 3) Sintering The composite material was placed in a special high-temperature sintering furnace for polytetrafluoroethylene and sintered at 345°C for 240 minutes. After cooling, a boron nitride interface assembled modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material was obtained. Its properties are shown in Table 1.
[0029] Example 3 Take 30 g of boron nitride (size 15 μm, thermal conductivity 750 W / (m·K)), 50 g of nickel foam (porosity 90%, number of pores per inch 20) and 1000 g of excess polytetrafluoroethylene emulsion (polytetrafluoroethylene particle size 200 nm, mass percentage 60%).
[0030] 1) Interface assembly 27g of boron nitride was added to 7.5g of polytetrafluoroethylene emulsion, and the mixture was stirred magnetically at 250 rpm for 10 hours until fully dispersed, to prepare an assembly solution with a ratio of boron nitride to polytetrafluoroethylene of 6:1. The metal skeleton was immersed in the assembly solution for 15 minutes under a vacuum degree of -0.03MPa, then taken out and placed in an oven at 110°C for 12 minutes to remove the solvent. The above immersion-drying steps were repeated 3 times.
[0031] 2) Matrix impregnation Add 3g of boron nitride to 97g of deionized water and disperse evenly. Then add 100g of boron nitride aqueous dispersion to 166.7g of polytetrafluoroethylene emulsion (the ratio of boron nitride to polytetrafluoroethylene is 3%), stir magnetically at 150 rpm for 5h until fully dispersed, and prepare the matrix liquid. Under a vacuum degree of -0.05MPa, immerse the interface-assembled foam metal skeleton in the matrix liquid for 20min, take it out, put it in an oven and dry it at 110℃ for 120min to remove the solvent. Repeat the above immersion-drying steps twice.
[0032] 3) Sintering The composite material was placed in a special high-temperature sintering furnace for polytetrafluoroethylene and sintered at 350°C for 300 minutes. After cooling, a boron nitride interface assembled modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material was obtained. The properties of the material are shown in Table 1.
Claims
1. A method for preparing a boron nitride interface assembled modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material, characterized in that: The following steps are involved: 1) Interface assembly: Add boron nitride to polytetrafluoroethylene emulsion and disperse it evenly to prepare assembly solution; Under vacuum, immerse the foam metal in the assembly liquid for 5 to 20 minutes, then take it out and dry it in a 70 to 110°C environment for 5 to 20 minutes to remove the solvent; repeat the immersion-drying steps several times; 2) Matrix impregnation: Boron nitride is added to deionized water and dispersed evenly to obtain a boron nitride dispersion; the boron nitride dispersion is then added to a polytetrafluoroethylene emulsion and dispersed evenly to prepare a matrix liquid; the metal foam after interface assembly is immersed in the matrix liquid under vacuum for 10 to 60 minutes, then taken out and placed in an environment of 80 to 120°C for drying for 30 to 120 minutes to remove the solvent; the immersion-drying steps are repeated several times; 3) placing the composite material obtained in step 2) in a sintering furnace, heating it to 330-390° C., sintering it for 60-390 min, cooling it in the furnace, and then taking it out to obtain a boron nitride interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material.
2. The method for preparing a boron nitride interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material as claimed in claim 1, characterized in that: In steps 1) and 2, the particle size of the boron nitride is 2-15 μm, and the thermal conductivity is 150-800 W / (m·K); the mass concentration of the polytetrafluoroethylene emulsion is 35%-65%, and the particle size of the polytetrafluoroethylene in the emulsion is 60-500 nm.
3. The method for preparing a boron nitride interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material as claimed in claim 1, characterized in that: In step 1), the solid-liquid mass ratio of boron nitride to polytetrafluoroethylene emulsion is 5:1~2:
1.
4. The method for preparing a boron nitride interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material as claimed in claim 1, characterized in that: In step 2), the concentration of the boron nitride dispersion is 0.5-5%, and the mass ratio of boron nitride to polytetrafluoroethylene in the matrix liquid is 1%-10%.
5. The method for preparing a boron nitride interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material as claimed in claim 1, characterized in that: In steps 1) and 2), the foam metal is one or more of nickel, copper, iron or iron-nickel alloy, with a porosity of 90-99% and a pore number per inch (PPI) of 10-110.
6. A boron nitride interface assembly modified foam metal-polytetrafluoroethylene interpenetrating phase lubricating material prepared by the method of claim 1.
Citation Information
Patent Citations
Porous foam metal based embedded type solid self-lubricating composite material and preparation method thereof
CN101906549A
Bicontinuous phase PTFE / metal composite material and preparation method thereof
CN116638794A
Polytetrafluoroethylene-based bicontinuous-phase water lubricating material as well as preparation method and application thereof
CN117487609A
Preparation method of large-size high-quality three-dimensional hexagonal boron nitride network
CN117737689A
Method of impregnating porous metal strip with polytetrafluoroethylene
FR1112137A
Cited By
High-thermal-conductivity polytetrafluoroethylene composite material and preparation method thereof
CN122483481A